Financial Sustainability and Reform Options for the Albanian Pension Fund - Treichel, Volker (IMF Working Papers; Working Paper ;, 2001)
This paper studies the financial sustainability of the Albanian pension fund and assesses possible options for its reform. The paper concludes that the pension fund is not sustainable in its current form and proposes for the urban scheme a combination of parametric changes to the existing pay-as-you-go system that would be conducive to broadening the contribution base and strengthening the financial performance of the pension fund. In addition, it proposes the establishment of a voluntary funded pillar in the urban scheme. For the rural scheme, the paper concludes that it should either be merged with the scheme for the urban self-employed or be replaced by a mandatory and funded second pillar. The paper also proposes administrative reforms to strengthen revenue collections.